Adherence and future discontinuation of tyrosine kinase inhibitors in chronic phase chronic myeloid leukemia. A patient-based survey on 1133 patients. Issue 10 (October 2015) - Breccia, Massimo; Efficace, Fabio; Sica, Simona; Abruzzese, Elisabetta; Cedrone, Michele; Turri, Diamante; Gobbi, Marco; Carella, Angelo Michele; Gozzini, Antonella; Usala, Emilio; Cavazzini, Francesco; Danise, Paolo; et al.
Highlights In CML patients, social support, psychological and subjective perceptions could influence adherence. Based on patient's survey, high rate of adherence to TKIs has been reported. The majority of patients would like to discuss more about discomfort, anxiety and fear of the future. Fifty-five percent of patients did not take the drug for less than 3 days a month. Forty-nine percent of patients wouldn't interrupt the therapy due to fear of losing all the results achieved.